User Satisfaction On I.T. Oriented Library Services: A Study on Selected College Libraries of Upper Assam - Anurag Borpatra Gohain; Akramul Haque (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
Information Technology has revolutionized the way we live, think or doing things. I.T. has changed the customary library scenario far from advanced than we thought of. Libraries are now equipped with various I.T. based services. The present study has sought to measure the users’ satisfaction on I.T. oriented services provided by some selected college libraries of upper Assam.